Gendered ethnic discrimination and the role of recruiter gender. A field experiment - Erlandsson Anni (SAGE Publications, 2025)
Relying on data from a large-scale field experiment in Sweden, this article studies discrimination in recruitment on the basis of gender and ethnicity combined with recruiter gender. The study includes 5641 job applications sent in response to advertised vacancies, and the employer callbacks to these. Gender and either a Swedish or a foreign-sounding name were randomly assigned to the applications, and recruiter gender was documented whenever available. Based on the callback rates, there is evidence of ethnic discrimination against foreign-named job applicants by both male and female recruiters. Also, male applicants with foreign-sounding names are discriminated more than female applicants with foreign-sounding names. Thus, the results show gendered ethnic discrimination in the Swedish labor market, and this does not appear to depend on recruiter gender in general. However, the patterns for gendered ethnic discrimination by recruiter gender vary across occupational categories.